Nevirapine loaded core shell gold nanoparticles by double emulsion solvent evaporation: invitro and in vivo evaluation - Dalvi, Bhagyashree R.; Siddiqui, Ejaz A.; Syed, Asad S.; Velhal, Shilpa M.; Ahmad, Absar; Bandivdekar, Atmaram B.; Devarajan, Padma V. (Current Drug Delivery, 2016)
Background: HIV/AIDS is a macrophage resident infection localized in the reticuloendothelial system and remote locations of brain and bone marrow. We present core shell nanoparticles of gold(AuNPs) and nevirapine(NVP) for targeted delivery to the multiple HIV reservoirs. The aim of the study was to design core shell NVP loaded AuNPs with high drug loading and to evaluate biodistribution of the nanoparticles in possible HIV reservoirs in vivo. A specific objective was to assess the possible synergy of AuNPs with NVP on anti-HIV activity in vitro. Method: Core shell nanoparticles were prepared by double emulsion solvent evaporation method and characterized. Results: Glyceryl monostearate-nevirapine-gold nanoparticles(GMS-NVP-AuNPs) revealed high entrapment efficiency (> 70%), high loading (similar to 40%), particle size < 250 nm and zeta potential -35.9 +/- 1.41mv and exhibited sustained release with good stability. Surface plasmon resonance indicated shell formation while SEM coupled EDAX confirmed the presence of Au. TEM confirmed formation of spherical core shell nanoparticles. GMS-NVP-AuNPs revealed low hemolysis (< 10 %) and serum stability upto 6 h. GMS-NVP-AuNPs exhibited rapid, high and sustained accumulation in the possible HIV reservoir organs, including the major organs of liver, spleen, lymph nodes, thymus and also remote locations of brain, ovary and bone marrow. High cell viability and enhanced uptake in PBMC's and TZM-bl cells were observed. While uptake in PBMC's proposed monocytes/macrophages enabled brain delivery. GMS-NVP-AuNPs demonstrated synergistic anti-HIV activity. Conclusion: The superior anti-HIV activity in vitro coupled with extensive localization of the nanoparticles in multiple HIV reservoirs suggests great promise of the core shell GMS-NVP-AuNPs for improved therapy of HIV.